2020
DOI: 10.1021/acssuschemeng.0c01341
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Production of Hypochlorous Acid over Pt/WO3 under Simulated Solar Light

Abstract: The production of hypochlorous acid (HClO) over a visible-light active photocatalyst was achieved for the first time in an aqueous solution of NaCl under simulated solar light. Approximately 17.6 μM of HClO was accumulated after 1 h of photoirradiation by employing the photocatalytic oxidation of Cl– with O2 reduction over the Pt cocatalyst-loaded WO3. The quantum efficiency of the HClO production was 2.3% at 420 nm. Moreover, the photoelectrochemical HClO production on the WO3 photoanode was also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In our previous work, we have reported that the Pt cocatalyst works as the active site for the O 2 reduction reaction during the photocatalytic production of HClO over Pt/WO 3 , both H 2 O and H 2 O 2 could be produced, and the H 2 O 2 was easy to react with HClO which led to a decrease in the concentration of the accumulated HClO (eqn (11)). 22 2Cl − → Cl 2 + 2e − , E 0 = +1.39 V vs. NHE (at pH = 0.0)Cl 2 + H 2 O ↔ H + + HClO + Cl − O 2 + 4H + + 4e − → 2H 2 O, E 0 = +1.23 V vs. NHE (at pH = 0.0)O 2 + 2H + + 2h + → H 2 O 2 , E 0 = +0.68 V vs. NHE (at pH = 0.0)HClO + 2e − + H + → Cl − + H 2 OHClO + H 2 O 2 → H + + Cl − + H 2 O + O 2 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we have reported that the Pt cocatalyst works as the active site for the O 2 reduction reaction during the photocatalytic production of HClO over Pt/WO 3 , both H 2 O and H 2 O 2 could be produced, and the H 2 O 2 was easy to react with HClO which led to a decrease in the concentration of the accumulated HClO (eqn (11)). 22 2Cl − → Cl 2 + 2e − , E 0 = +1.39 V vs. NHE (at pH = 0.0)Cl 2 + H 2 O ↔ H + + HClO + Cl − O 2 + 4H + + 4e − → 2H 2 O, E 0 = +1.23 V vs. NHE (at pH = 0.0)O 2 + 2H + + 2h + → H 2 O 2 , E 0 = +0.68 V vs. NHE (at pH = 0.0)HClO + 2e − + H + → Cl − + H 2 OHClO + H 2 O 2 → H + + Cl − + H 2 O + O 2 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, H 2 O and H 2 O 2 will be competitively produced during the ORR, and the production of H 2 O 2 will lead to the decomposition of HClO, as shown in eqn (10). 22 Therefore, we investigated the production of H 2 O 2 on Mn, Pt, and Pt-Mn during the oxidative photoelectrochemical HClO production using the WO 3 /FTO electrode as the photoanode and MnO x /FTO, Pt/FTO, or Pt-Mn/FTO as the cathode in a two-compartment cell. Gaseous N 2 was bubbled into the anode chamber and O 2 was bubbled into the cathode chamber at a flow rate of 1 mL min −1 .…”
Section: Effect Of the Pt-mn Cocatalyst On Hclo Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opposite to the TiO 2 , the Cl − are adsorbed well on the ZnO surface, having a positive charge [ 83 , 84 , 85 ] and enhancing the formation rate of ROS due to the hindered recombination of photoinduced e CB − and h VB + [ 83 ]. Significant conversion of Cl − by h VB + to HClO has been reported in some cases [ 82 , 86 , 87 ]. The degradation of HClO via reaction with e CB − , or superoxide radical anions (O 2 •− ) also results in the formation of • OH [ 87 , 88 ], which may explain the increased r 0 7-HC for ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…Significant conversion of Cl − by h VB + to HClO has been reported in some cases [ 82 , 86 , 87 ]. The degradation of HClO via reaction with e CB − , or superoxide radical anions (O 2 •− ) also results in the formation of • OH [ 87 , 88 ], which may explain the increased r 0 7-HC for ZnO. Active chlorine species formation and photocatalytic reactions are complex, depending on many parameters [ 88 , 89 , 90 ], and require further investigation.…”
Section: Resultsmentioning
confidence: 99%